Pathogenesis of autoimmunity in common variable immunodeficiency - Warnatz, Klaus; Voll, Reinhard E. (Frontiers in Immunology, 2012)
Common variable immunodeficiency (CVID) presents in up to 25% of patients with autoimmune (AI) manifestations. Given the frequency and early onset in patients with CVID, AI dysregulation seems to be an integral part of the immunodeficiency. Antibody-mediated AI cytopenias, most often affecting erythrocytes and platelets, make up over 50% of these patients. This seems to be distinct from mainly cell-mediated organ specific autoimmunity. Some patients present like patients with AI lymphoproliferative syndrome (ALPS). Interestingly, in the majority of patients with AI cytopenias the immunological examination reveals a dysregulated B and T cell homeostasis. These phenotypic changes are associated with altered signaling through the antigen receptor which may well be a potential risk factor for disturbed immune tolerance as has been seen in STIM1 deficiency. In addition, elevated BAFF serum levels in CVID patients may contribute to survival of autoreactive B cells. Of all genetic defects associated with CVID certain alterations in TACI, CD19 and CD81 deficiency have most often been associated with AI manifestations. In conclusion, autoimmunity in CVID offers opportunities to gain insights into general mechanisms of human autoimmunity.